Exploration of a Au(i)-mediated three-component reaction for the synthesis of DNA-tagged highly substituted spiroheterocycles. Issue 40 (5th October 2017) - Klika Škopić, Mateja; Willems, Suzanne; Wagner, Bernd; Schieven, Justin; Krause, Norbert; Brunschweiger, Andreas
Abstract : A gold(i )-mediated reaction to a DNA-tagged spirocycle, and the tolerance of different nucleic acids to the reaction conditions are demonstrated. Abstract : We demonstrate a Au(i )-mediated three-component reaction to DNA-tagged highly substituted 6-oxa-1, 2-diazaspiro[4.4]nonanes from either DNA-coupled aldehydes, hydrazides, or alkynols. The choice of the starting material coupled to the DNA tag was critial for the purity of the product as the DNA-aldehyde conjugate yielded the purest products, whereas the alkynol- and hydrazide conjugates returned complex product mixtures. The reaction was compatible with thymine-, cytosine-, and, surprisingly, with adenine-DNA, while guanine-containing DNA strands were degraded under the reaction conditions.